Prevalence of mental nerve injury in facial fractures: a 3 year retrospective study - Shah, Navin S.; Panchal, Karan V.; Agrawal, Pratik (International Journal of Research in Medical Sciences, 2019)
Background: Mandibular fracture is the most common facial bone fracture. Fractures occurring at the Para symphysis region frequently results in mental nerve injury, due to which anaesthesia or paraesthesia of the skin and mucous membrane within the distribution of mental nerve may be observed and may cause reduced quality of life for patients. Aim of this study was to retrospectively analyse and evaluate the prevalence rate of mental nerve injury in patients that reported to the department of oral and maxillofacial surgery, managed conservatively or open reduction and internal fixation method during the last 3 years Methods: Patients with neurosensory deficit following para symphysis fracture were recorded, statistically analyzed and results and observation were prepared from it. Results: The patients with age group 21-30 diagnosed with para symphysis fracture constituted 25% of all operated case and were found to be more associated with midface and angle fracture. Etiology behind the trauma was mostly as a result of RTA. Neurosensory disturbances as a result of mental nerve injury were found to be associated in 20.89% case, out of which in most of the cases, it gradually recovered within a duration of 7-15 days. Conclusions: RTA’s have been a prime cause for para symphysis fracture, which may at times accompany neurosensory deficit following trauma or may occur post-surgery, has been found to cause troublesome sequelae and reduced quality of life. Moreover, further research study needs to be carried out over a larger time span having a larger group of patients.